Between extrativism and peasant agriculture: differentiation of rural settlements in the Bolivian Amazon - Stoian, Dietmar (2000)
The economy of the northern Bolivian Amazon has historically been based on rubber and other non-timber forest products (NTFPs). In the late 19th century, the upcoming rubber boom lead to the establishment of rubber estates. Following World War l, a first rubber crisis forced sorne estate owners to abandon their land, favouring the emergen ce of independent communities. A second rubber crisis after World War n, along with the Agrarian Reform in 1953, accelerated the disintegration of rubber estates and the foundation oC independent commullities. In the early 1990s, the conclusive halt of Bolivian rubber production fuelled rural-urban migration and the differentiation of rural settlements. This paper examines the evolution from pure rubber estates to a wide array of settlement types. A settlement typology distinguishes four types of estates and six types of independent communities with varying trade-offs between extractivism and peasant agricu1ture. The findings have important implications for NTFP-based development. First, extraction-based Iivelihoods are socially acceptable only when access to Ibasic services, like schooling, health care, and transportation is ensured. Second, in the region's remote areas the supply of such services needs to rely on a forest concession system within which the prívate sector bears the investments needed. Finally, indigenous communities participating .in NTFP trade need to demarcate their sphere in between the remo te forest concessions and the non-tribal peasantry in the vicinity of town.